Protocol for the Electroporation of Neurospora Spheroplasts - Gregory O. Kothe; Stephen J. Free (Fungal Genetics Reports, 1996)
A protocol for electroporating Neurospora strains is described. This protocol uses spheroplasts for transformation rather than germinated conidia with enzyme-weakened walls. High efficiency transformation is obtained with this system even with batches of Novozyme234 which worked poorly in the PEG based protocol.